Computer Modelling Studies of MPO4, LiMPO4 and NaMPO4 (M: Fe, Co, Mn) Polymorphs - Lethole, Ndanduleni Lesley (University of Limpopo, 2016)
Refer to the document
Thesis (Ph.D. (Physics)) -- University of Limpopo, 2016
Keywords: Polymorphs; Computer modelling studies; Physics